Acute physical exercise increases APPL1/PI3K signaling in the hypothalamus of lean mice - Gaspar, Rafael Calais; Muñoz, Vitor Rosetto; Kuga, Gabriel Keine [UNESP]; Nakandakari, Susana Castelo Branco Ramos; Crisol, Barbara Moreira; Lenhare, Luciene; Breda, Leonardo; Botezelli, José Diego; Sant'Ana, Marcella Ramos; da Silva, Adelino S. R.; Cintra, Dennys Esper; Moura, Leandro Pereira de; et al. (Wiley, 2019)
Adiponectin is an adipokine that acts in the control of energy homeostasis. The adaptor protein containing the pleckstrin homology domain, phosphotyrosine-binding domain, and leucine zipper motif 1 (APPL1) is a key protein in the adiponectin signaling. The APPL1 mediates a positive effect on the insulin signaling through the interaction with the phosphoinositide 3-kinase (PI3K). Thus, the present study aimed to explore the effects of an acute physical exercise session on the hypothalamic adiponectin signaling. Firstly, using bioinformatics analysis, we found a negative correlation between hypothalamic APPL1 mRNA levels and food consumption in several strains of genetically diverse BXD mice. Also, the mice and the human database revealed a positive correlation between the levels of APPL1 mRNA and PI3K mRNA. At the molecular level, the exercised mice showed increased APPL1 and PI3K (p110) protein contents in the hypothalamus of Swiss mice. Furthermore, the exercise increases co-localization between APPL1 and PI3K p110 predominantly in neurons of the arcuate nucleus of hypothalamus (ARC). Finally, we found an acute exercise session reduced the food intake 5 hr after the end of fasting. In conclusion, our results indicate that physical exercise reduces the food intake and increases some proteins related to adiponectin pathway in the hypothalamus of lean mice.
Keywords: adiponectin; APPL1; hypothalamus; physical exercise; PI3K